2019
DOI: 10.2147/ijn.s222797
|View full text |Cite
|
Sign up to set email alerts
|

<p>cRGD-Conjugated Fe<sub>3</sub>O<sub>4</sub>@PDA-DOX Multifunctional Nanocomposites for MRI and Antitumor Chemo-Photothermal Therapy</p>

Abstract: Background: Photothermal therapy (PTT) has great potential in the clinical treatment of tumors. However, most photothermal materials are difficult to apply due to their insufficient photothermal conversion efficiencies (PCEs), poor photostabilities and short circulation times. Furthermore, tumor recurrence is likely to occur using PTT only. In the present study, we prepared cyclo (Arg-Gly-Asp-d-Phe-Cys) [c(RGD)] conjugated doxorubicin (DOX)-loaded Fe 3 O 4 @polydopamine (PDA) nanoparticles to develop a multifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Conjugation of these NPs to chemotherapeutic drugs did not only effectively kill tumor cells via active targeting, but also inhibited tumor growth using near-infrared (NIR) irradiation due to the photothermal activity of the NPs (Fan et al, 2019). In another study, Fe 2 O 3 -gold NPs were observed to accumulate within the tumor mass instead of other organs in a colon cancer model, while also enhancing the tumor detection selectivity as MRI contrast agents in a pancreatic cancer model (Kumagai et al, 2010).…”
Section: Nanomedicines and Colorectal Cancermentioning
confidence: 98%
“…Conjugation of these NPs to chemotherapeutic drugs did not only effectively kill tumor cells via active targeting, but also inhibited tumor growth using near-infrared (NIR) irradiation due to the photothermal activity of the NPs (Fan et al, 2019). In another study, Fe 2 O 3 -gold NPs were observed to accumulate within the tumor mass instead of other organs in a colon cancer model, while also enhancing the tumor detection selectivity as MRI contrast agents in a pancreatic cancer model (Kumagai et al, 2010).…”
Section: Nanomedicines and Colorectal Cancermentioning
confidence: 98%
“…57 However, the use of PTT alone has limitations: light penetration depth is limited, it resulted in incomplete elimination of cancer cells, and the residual edge of the treatment area may lead to the recurrence of the disease. 58,59 Immunotherapy plays an important role in the treatment of metastatic tumors. The combination of physical effect and influence can not only eliminate tumor cells through hyperthermia, but also improve the release of antigens in the body to enhance the immune response.…”
Section: Metal Oxides Materials and Chalcogenides As Functional Compo...mentioning
confidence: 99%
“…This neurotransmitter can self-aggregate to form polydopamine (PDA) under speci c conditions. Because of the high biocompatibility and biodegradability, PDA has been widely used in the camou age of nanoparticles and various biomedical applications [12].PDA-coated magnetic nanostructureshave good thermal stability, photothermal conversion e ciencies, pH responsiveness,biocompatibility and low genotoxicity [13][14][15].Some studies have shown that the use of PDA modi cation can signi cantly improve the biocompatibility of Fe 3 O 4 , but it still shows a certain degree of cytotoxicity. Therefore, the development of new modi cation methods is an urgent need for the clinical application of Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%